PHGDH drives 5-FU chemoresistance in colorectal cancer through the Hedgehog signaling - Caterina Mancini; Giulia Lori; Gianluca Mattei; Marta Iozzo; Dayana Desideri; Fabio Cianchi; Laura Fortuna; Federico Passagnoli; Daniela Massi; Filippo Ugolini; Luca Messerini; Salvatore Piscuoglio; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Background Phosphoglycerate dehydrogenase (PHGDH) is the rate-limiting enzyme in the de novo Serine synthesis pathway (SSP), a highly regulated pathway overexpressed in several tumors. Specifically, PHGDH expression is dynamically regulated during different stages of tumor progression, promoting cancer aggressiveness. Previously, we demonstrated that high Serine (Ser) availability, obtained by increased exogenous uptake or increased PHGDH expression, supports 5-Fluorouracil (5-FU) resistance in colorectal cancer (CRC). Beyond its metabolic role in sustaining Ser biosynthesis, different “non-enzymatic roles” for PHGDH have recently been identified. The present study aims to investigate non-enzymatic mechanisms through which PHGDH regulates 5-FU response in CRC. Methods Overexpression and gene silencing approaches have been used to modulate PHGDH expression in human CRC cell lines to investigate the role of this enzyme in 5-FU cellular response. Identified mechanisms have been validated in selected 5-FU resistant cell lines, CRC patients-derived tumor tissue samples, and patients-derived 3D organoids. Transcriptomic analysis was performed on wild-type and PHGDH-silenced cell lines, allowing the identification of pathways responsible for PHGDH-mediated 5-FU resistance. The relevance of identified genes was validated in vitro and in vivo in a CRC xenograft model. Results PHGDH expression is highly variable among CRC tissues and patient-derived 3D organoids. A retrospective analysis of CRC patients highlighted a correlation between PHGDH expression and therapy response. Coherently, the modulation of PHGDH expression by gene silencing/overexpression affects 5-FU sensitivity in CRC cell lines. Transcriptomic analysis on CRC cell lines stably silenced for PHGDH evidenced down regulation in Hedgehog (HH) pathway. Accordingly, in vitro and in vivo studies demonstrated that the combined treatment of 5-FU and HH pathway inhibitors strongly hinders CRC cell survival and tumor growth in CRC xenograft models. Conclusions PHGDH sustains 5-FU resistance in CRC by mediating the upregulation of the HH signaling; targeting the here identified PHGDH-HH axis increases 5-FU susceptibility in different CRC models suggesting the 5-FU/HH-inhibitors combinatorial therapeutic strategy as a valid approach to counteract drug resistance in CRC.